2020
DOI: 10.3390/s20072104
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Exerted Hand Force via Force Myography to Interact with a Biaxial Stage in Real-Time by Learning Human Intentions: A Preliminary Investigation

Abstract: Force myography (FMG) signals can read volumetric changes of muscle movements, while a human participant interacts with the environment. For collaborative activities, FMG signals could potentially provide a viable solution to controlling manipulators. In this paper, a novel method to interact with a two-degree-of-freedom (DoF) system consisting of two perpendicular linear stages using FMG is investigated. The method consists in estimating exerted hand forces in dynamic arm motions of a participant using FMG si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Since FMG signals can read muscle contractions during such activities, it can be a viable tool for predicting worker's intended interactions or applied forces [14]. Therefore, a few studies were conducted to determine isometric hand forces, dynamic forces in motion via FMG signals [15], [16]. Although the study in [16] showed impressive results in recognizing applied forces in dynamic motion during HRI, it had a few shortcomings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since FMG signals can read muscle contractions during such activities, it can be a viable tool for predicting worker's intended interactions or applied forces [14]. Therefore, a few studies were conducted to determine isometric hand forces, dynamic forces in motion via FMG signals [15], [16]. Although the study in [16] showed impressive results in recognizing applied forces in dynamic motion during HRI, it had a few shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a few studies were conducted to determine isometric hand forces, dynamic forces in motion via FMG signals [15], [16]. Although the study in [16] showed impressive results in recognizing applied forces in dynamic motion during HRI, it had a few shortcomings. First, a separate regression model was trained for predicting forces applied by each participant for one specific motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating isometric or dynamic hand force/torque using FMG signals via FSRs were found favorable to FT sensors [ 28 , 29 , 30 ]. Recently, measuring force via FMG bio signals during physical human robot interactions (pHRI) between human participants and a linear robot was found effective for intra-session evaluation using traditional ML algorithms [ 31 ]. However, intra-session FMG-based pHRI required collecting adequate labelled training data, which was biased and impractical in real scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Force Myography (FMG) is a technique to quantify changes in the volume of a limb resulting from muscle contractions and relaxations (Xiao and Menon, 2014 ). This biosignal has been employed in a variety of applications including gesture recognition, control of exoskeletons, prostheses, and linear actuators, and estimation of user-applied forces to manipulate planar linear actuators (Xiao et al, 2014 ; Cho et al, 2016 ; Sakr and Menon, 2016a , b , 2017 , 2018 ; Jiang et al, 2017 ; Sadarangani and Menon, 2017 ; Zakia and Menon, 2020 ). Force myography from upper-limbs could be collected using lightweight, compact, and unobtrusive bands wrapped around wrist, forearm, and/or upper arm, which makes it an attractive technique for developing wearables.…”
Section: Introductionmentioning
confidence: 99%